Analisis Financial Distress Dengan Metode Altman, Zmijewski Dan Springate Untuk Memprediksi Kebangkrutan Perusahaan Di Indeks Saham Syariah Indonesia - Chua, Meli; Ananda Rustam, Triana (Efektor, 2023)
The research aims to determine the financial condition of manufacturing companies in the consumer goods sub-sector listed in the Indonesian Sharia Stock Index using the Altman, Zmijewski, and Springate methods. The research is conducted using a descriptive quantitative method, with a sample size of 13 companies. The results of the research indicate that: 1) based on the Altman method, there are companies experiencing financial distress, namely FOOD for the period of 2017-2020, INDF for the period of 2020, KAEF for the period of 2017 and 2018-2021, and UNVR for the period of 2021. 2) Based on the Zmijewski method, there are companies experiencing financial distress, namely FOOD for the period of 2017 and UNVR for the period of 2021. 3) Based on the Springate method, there are companies experiencing financial distress, namely FOOD for the period of 2017-2020, HOKI for the period of 2021, ICBP for the period of 2021, INDF for the period of 2018-2021, KAEF, PCAR, and WOOD for the period of 2017-2020.